Pengaruh Servant Leadership dan Human Capital Terhadap Kepuasan Kerja Dengan Employee Engagement Sebagai Variabel Mediasi - Muhammad Syarifuddin Aziez; Sidiq Permono Nugroho (PRODI AKUNTANSI FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TJUT NYAK DHIEN (UTND), 2023)
This study aims to examine the effect of Servant Leadership and Human Capital on Job Satisfaction with Employee Engagement as a mediating variable. The population in this study are employees at PT. Polychem Indonesia with data collection using a questionnaire to 75 respondents. The data analysis tool in this study used the Smart PLS software version 3.2.9, with the outer model test and inner model test. The results of this study indicate that (1) Employee Engagement has a significant negative effect on Job Satisfaction. (2) Human Capital has a significant positive effect on Employee Engagement. (3) Human Capital has a significant negative effect on job satisfaction. (4) Servant Leadership has a significant positive effect on Employee Engagement. (5) Servant Leadership has a significant negative effect on Job Satisfaction. (6) Human Capital has a significant negative effect on Job Satisfaction mediated by Employee Engagement. (7) Servant Leadership has a significant negative effect on Job Satisfaction mediated by Employee Engagement.